Pathogenesis of large vessel vasculitis: Implications for disease classification and future therapies. (February 2019) - Harky, Amer; Fok, Matthew; Balmforth, Damian; Bashir, Mohamad
Despite being recognised over a century ago, the aetiology and pathogenesis of large vessel vasculitis (LVV) still remains elusive. Takayasu's arteritis (TA) and giant cell arteritis (GCA) represent the two major categories of LVV, each with distinctive clinical features. Over the last 10 years an increased understanding of the immunopathogenesis of the inflammatory cascade within the aortic wall has revived the view that LVVs may represent subtypes of the same pathological process, with implications in the treatment of this disease. In this review, the histological, genetic and immunopathological features of TA and GCA will be discussed and the evidence for a common underlying disease mechanism examined. Novel markers of disease activity and therapies based on advances in our understanding of the immunopathogenesis of these conditions will also be discussed.